2013
DOI: 10.4103/0019-5413.114918
|View full text |Cite
|
Sign up to set email alerts
|

Lateral malleolus hook plate for comminuted Weber A and B fractures: A retrospective study

Abstract: Background:The goal of managing the comminuted fracture of lateral malleolus is to restore length, rotation and alignment which might be more challenging with extensive comminution around the area of the distal tip. The common osteosynthesis techniques such as the one-third tubular plate, tension band wiring, K-wires, screws, or intramedullary nail may be insufficient in cases with a comminuted lateral malleolus. The anatomical hook plate is an alternative implant in such cases. We present our results of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Zhong et al [ 13 ] showed an AOFAS score of 74.5 in patients aged 18-64 years after ORIF. Furthermore, Zhenhua et al [ 14 ] retrospectively reviewed 20 patients with fractures of the distal lateral malleolus and found an AOFAS score of 78 in an age group similar to that in our study. The mean follow-up in this study was 21.4 months (range, 16-27 months).…”
Section: Discussionsupporting
confidence: 87%
“…Zhong et al [ 13 ] showed an AOFAS score of 74.5 in patients aged 18-64 years after ORIF. Furthermore, Zhenhua et al [ 14 ] retrospectively reviewed 20 patients with fractures of the distal lateral malleolus and found an AOFAS score of 78 in an age group similar to that in our study. The mean follow-up in this study was 21.4 months (range, 16-27 months).…”
Section: Discussionsupporting
confidence: 87%
“…In studies that present only lateral malleolar fracture open surgery results, the AOFAS scores are close to the present results. 16 In the case series by Zhenhua et al, 16 it can be seen that patients with low scores have additional traumas. We believe that this difference in AOFAS scores may be linked to morbidity caused by the additional trauma in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Using cerclage wires and lag screw fixation, Bajwa and Gantz 39 reported a 100% rate of union in 52 patients. Zhenhua et al 40 achieved a 100% rate of union in 20 patients using hook plates. Comparatively, results from this study, using cannulated intramedullary screw fixation, achieved a 98% rate of union in 45 patients, with an average time to union of 10 weeks.…”
Section: Discussionmentioning
confidence: 99%